2019
DOI: 10.1089/neu.2018.5854
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Endocannabinoid System in Ameliorating Motivation for Alcohol Drinking and Negative Behavioral Affect after Traumatic Brain Injury in Rats

Abstract: Traumatic brain injury (TBI) is associated with psychiatric dysfunction-including pain, cognitive impairment, anxiety, and increased alcohol use. We previously demonstrated that inhibiting endocannabinoid degradation post-TBI with JZL184 attenuates neuroinflammation and neuronal hyperexcitability at the site of injury and improves neurobehavioral recovery. This study aimed to determine the effect of JZL184 on post-TBI behavioral changes related to psychiatric dysfunction and post-TBI neuroadaptations in brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
3
14
0
Order By: Relevance
“…Thus, it will be important to investigate how prior history of alcohol affects subsequent blast‐induced changes to alcohol intake patters and sensitivity in future studies. Indeed, alcohol intake occurring peri‐TBI exposure in male rats resulted in worse outcomes as compared to rats with TBI but no previous history of alcohol (Fucich et al, 2019; Mayeux et al, 2015; Teng et al, 2015), supporting the potential for alcohol to impair recovery and/or exacerbate injury.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it will be important to investigate how prior history of alcohol affects subsequent blast‐induced changes to alcohol intake patters and sensitivity in future studies. Indeed, alcohol intake occurring peri‐TBI exposure in male rats resulted in worse outcomes as compared to rats with TBI but no previous history of alcohol (Fucich et al, 2019; Mayeux et al, 2015; Teng et al, 2015), supporting the potential for alcohol to impair recovery and/or exacerbate injury.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found no major effect of lateral FPI on performance in the open-field test. Previously, Kim et al 39 and Fucich et al 40 assessed rats with lateral FPI at D4 and D7 postinjury, respectively, and found that the injured rats spent less time than controls exploring the center of the open field. Similarly, Schultz et al 14 reported that rats with severe lateral FPI spent slightly less time than sham-operated controls in the inner arena at 1 and 3 months, but not at 6 months post-TBI; however, there was no difference between the epileptic and nonepileptic animals.…”
Section: Discussionmentioning
confidence: 99%
“…A full systematic review has not been performed on pre-clinical studies of anxiety-related behaviors following TBI [but see (Semple et al, 2019) for an excellent summary]. The most consistency is with the FPI model, where increased anxiety-like behaviors are observed in most studies in both rats (Das et al, 2019;Dobrachinski et al, 2019;Fucich et al, 2019;Beitchman et al, 2020;Lapinlampi et al, 2020;Barretto et al, 2021) and mice (Tan et al, 2020;Tapp et al, 2020;Bhowmick et al, 2021), although in some studies this result is dependent on the time testing took place after injury. There is limited evidence from some CCI studies that results and conclusions from anxiety testing may depend on the time after injury at which behavioral testing takes place, or on the specific behavioral test employed Popovitz et al, 2019).…”
Section: Anxiety-like Symptoms Post-tbi In Rodentsmentioning
confidence: 99%